Artificial Intelligence Enhanced Learning Management System: Supporting Merdeka Belajar-Kampus Merdeka (MBKM) at a State University in Indonesia - Anisah, Lina; Yawan, Hendri; Marhamah, Marhamah (LPPPIPublishing, 2024)
This research aims to develop an e-learning system integrated with ChatGPT in enhancing students' learning outcomes within the Merdeka Belajar Kampus Merdeka (MBKM). By adopting the Analyze, Design, Develop, Implement, and Evaluate (ADDIE) approach, this study indicates a remarkable 80% satisfaction rate among users of the e-learning platform. Despite focusing on the e-learning development stage and content preparation, there remains an avenue for further investigation, specifically in the realm of classroom action research. The implementation of this e-learning portal stands as a significant milestone in educational technology, emphasizing accessibility, adaptability, and cost-efficiency, offering a durable platform for educational content. User feedback underlines the success of this development, endorsing its continued usage and potential for further advancements. This research not only addresses the immediate effectiveness of integrating ChatGPT into e-learning but also showcases the potential for continual enhancement and the ongoing evolution of educational technologies within the MBKM initiative at Universitas Sembilanbelas November Kolaka.